Postharvest qualities and metabolic responses of hydro- cooled rockmelon (Cucumis melo L. reticulatus cv Glamour) after differential storage durations - Zainal, Bokhary (2018)
Harvested rockmelon often accumulates a considerable amount of heat from the high field temperature which accelerates the respiration, metabolic changes and thus shortens the market life of the fruit. The beneficial effects of hydro-cooling to rapidly reduce the core temperature in order to maintain fruit quality during postharvest storage has been reported on various fruits. Therefore, the main objective of this study was to evaluate the cooling time (CT) which characterize the performance of hydro-cooled rockmelon during cold storage. Three experiments were conducted to determine (i) quality and postharvest performances of hydro-cooled rockmelon (ii) antioxidant enzymes activity and histological structure of hydro-cooled rockmelon and (iii) phytochemical content, in vitro antioxidant activities and metabolite composition of hydro-cooled rockmelon. To achieve the best cooling time, rockmelon fruit (25.5 °C initial temperature) was hydro-cooled to 14.8 and 9.4 °C to attain 1/2 and 3/4 CT, respectively prior to storage at 13 °C cold room of 85% relative humidity along with non-hydro-cooled fruit (0 CT) as control. Results showed that 1/2 CT was effective in slowing down weight loss and increment of soluble solids concentration, preserving higher chroma intensity of pulp colour and turgor pressure of rind and pulp firmness, and maintaining the citric acid content as compared to the others treatment during rockmelon storage. The significant weight loss in the control and 3/4 CT hydro-cooled rockmelon had influenced cell rigidity as dehydration caused the impact in a loss of cell turgor. During storage, the ascorbate peroxidase, peroxidase and superoxide dismutase enzymes activity were higher for 1/2 CT rockmelon. The significant induction of these antioxidative enzymes activity corresponded to lower lipid peroxidation as measured by malondialdehyde content. The less induction of antioxidative enzyme activity in 3/4 CT and control rockmelon pulp exposed the fruits to deleterious effect of free radicals. The severity of cell membranes disorder in structural characteristics was in line with higher malondialdehyde content due to less tolerance to oxidative stress in 3/4 CT and control rockmelon. To better understand the metabolic changes, untargeted metabolite properties were studied through Nuclear Magnetic Resonance (NMR)-based metabolomics approach to visualize variations in metabolic profile of hydro-cooled rockmelon during cold storage. Overall, sugars and amino acids were appreciably affected by hydro-cooling application. The high intensity of phenylalanine, tryptophan and tyrosine appear to be associated with biosynthesis of secondary metabolites and cold tolerance since their present were altered in 1/2 CT rockmelon, relative to the control and 3/4 CT hydro-cooled rockmelon. Noticeably, less accumulation of sucrose during advanced cold storage in control and 1/2 CT hydro-cooled rockmelon rind might reduce the cell metabolism and fruit resistibility in response to cold storage since it influences the cell structural support and protection against reactive oxygen species (ROS). In short, the 1/2 CT of hydro-cooling application could be considered as the optimum CT level for rockmelon fruit in preserving physico-chemical quality and thus, extending the storage life of rockmelon fruit.